Galectina-3, AFAP1-L1 e WASP na invasão e multiplicação de Trypanosoma cruzi e caracterização biológica da proteína P21-His6 - Machado, Fabrício Castro (2014)
The parasitism of cellular organisms is a topic of high relevance to human health and is under constant investigation. The process by which the flagellate protozoan Trypanosoma cruzi invades the host cells, thus causing the Chagas disease, is still not fully understood. In this work we study the role of AFAP-1L1, galectin-3 and WASP proteins on host cell invasion and characterize the biological functions of the P21 recombinant form, called P21-His6. The AFAP-1L1, galectin-3 and WASP proteins participate in numerous biological activities on the host cell, while the P21 protein, a recently characterized protein present in the membrane of T. cruzi, is presented in all developmental stages of the parasite. We assessed the involvement of galectin-3 in the intracellular traffic of T. cruzi by immunofluorescence tracking, and the role of the other host proteins by knockdown cell lines. The biological activities of P21-His6 were studied by selection of specific bacteriophages ligands with Biopanning technique, with implantation of sponges in Balb/c animals, treating or nor with P21-His6, and evaluating chemotaxis response when treating C57Bl/6 animals. We observed that galectin-3 is present in approximately 20% of cellular invasion events, forming structures containing polarized galectin-3 (G3CS) that fades over time. We also observed that AFAP-1L1 seems to have some importance in controlling early multiplications, and that reduction of WASP protein expression seems to facilitate parasite proliferation in parallel to the reduction of invasion. Thus, we conclude that these proteins are important for establishing T. cruzi infection. We observed that the P21-His6 has anti-angiogenic activity and capacity for cellular recruitment probably through interaction with the CXCR4 receptor especially of activated macrophages and neutrophils. We also obtained mimetic CXCR4 bacteriophages capable of specifically binding to P21-His6 and reducing its biological effects in vitro. Thus we conclude that P21-His6 has high chemotactic capacity that can be inhibited by specific ligands, and may have therapeutic anti-angiogenic activity. Together these results may open the door to novel therapeutic interventions.